The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s10278-004-1016-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Human Visual System Model to Predict Observer Performance with CRT vs LCD Display of Images

Abstract: This Project evaluated a human visual system model (JNDmetrix) based on just noticeable difference (JND) and frequency-channel vision-modeling principles to assess whether a Cathode ray tube (CRT) or a liquid crystal display (LCD) monochrome display monitor would yield better observer performance in radiographic interpretation. Key physical characteristics, such as veiling glare and modulation transfer function (MTF) of the CRT and LCD were measured. Regions of interest from mammographic images with masses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…It is possible that the higher peak of luminance in the raster scan CRT display increased mask intensity, relative to the other two monitors, thereby resulting in the greater metacontrast-masking effect. Another possibility is that clarity of the stimuli was related to a stronger masking effect in the raster scan CRT display, because the CRT display produced blurry images, relative to the LCD display (Krupinski et al, 2004), resulting in a greater effect of contour proximity (Alpern, 1953) under the critical masking period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the higher peak of luminance in the raster scan CRT display increased mask intensity, relative to the other two monitors, thereby resulting in the greater metacontrast-masking effect. Another possibility is that clarity of the stimuli was related to a stronger masking effect in the raster scan CRT display, because the CRT display produced blurry images, relative to the LCD display (Krupinski et al, 2004), resulting in a greater effect of contour proximity (Alpern, 1953) under the critical masking period.…”
Section: Resultsmentioning
confidence: 99%
“…LCDs have many advantages over raster scan CRT displays in terms of weight, volume, and electrical power consumption (Menozzi, Näpflin, & Krueger, 1999). Modern LCDs are also superior to raster scan CRT displays in several aspects of static image quality (Krupinski et al, 2004). Indeed, it has been reported that in terms of assessment of quality, LCDs provide higher quality than do raster scan CRT displays (Tourancheau, Callet, & Barba, 2008).…”
mentioning
confidence: 99%
“…Subsequently, significant developments in medical-grade display technology were started in the late 1980s and continue today. The early displays were cathode ray tube, [26][27][28] but today liquid crystal displays (LCDs) and variants such as organic light-emitting diodes are the norm in most radiology reading rooms. 29,30 Some of the key display parameters that have guided the development of these displays are directly related to the perceptual requirements of radiologists, the digital nature of the images, the complex nature of anatomic structures, and lesions in the images.…”
Section: Modalities Of Teleradiologymentioning
confidence: 99%
“…1 From the Department of Radiology, Ö rebro University Hospital, SE-701 85, Ö rebro Sweden. 2 From the Department of Radiology, Sahlgrenska University Hospital, SE-413 45, Gothenburg Sweden. 3 …”
mentioning
confidence: 99%
“…This is supported by several studies. 2,3 We wished to test the null hypothesis that there is no significant difference in a calculated image quality factor between contrast-detail phantom images displayed on a consumer-grade color LCD display and a medical-grade monochrome LCD display having the same resolution. We also wished to test the null hypothesis that there is no significant difference in diagnostic image quality between clinical radiographs of the lumbar spine displayed on the same monitors.…”
mentioning
confidence: 99%